文化传承、旅游推广与政治诉求：论“妆艺大游行”的发展与演变 = Cultural heritage, tourism promotion and political demands : shift and development in Chingay Parade - 陈诗琪 Tan, Shi Qi (2017)
妆艺大游行，又称“粧艺大游行”（简称“妆艺”） ，在今年已迈入了第四十五年。如今的妆艺，已成为了亚洲最大的夜间游行及花车表演。1973年2月4日，为配合华人农历新年的欢庆，妆艺正式在惹兰勿刹区举行第一次游行，并赢得热烈回响。此后，妆艺成为新加坡一年一度的游行盛典。为配合本地各族群众，妆艺渐渐从单单为华人庆祝的农历新年表演蜕变为展示及推广新加坡多元文化的舞台。在旅游促进局成为了妆艺的主办单位之后，妆艺就逐渐走向积极吸引游客的商业化表演。另外，新加坡政府也通过这场大型表演舞台向新加坡人宣导某些政策或灌输一些思想意识，以达到某种政治诉求。本文将通过梳理妆艺大游行的历史脉络，进一步揭示妆艺大游行的来源、发展及演变，思考并从而探讨新加坡人在受到妆艺各方面的改变之后所出现的态度上的转变。最后综合几点思考，推测未来的发展趋势。This year, Chingay Parade has entered its forty-fifth year since the initiation from 1973. Today, Chingay has evolved to become the largest night parade in Asia. To celebrate Lunar New Year, Chingay was first held at Jalan Besar neighbourhood on 4 February 1973. It was well received and hence the organisers decided to celebrate the Chingay Parade annually. Due to people’s suggestions, it gradually changed from a Lunar New Year celebration for the Chinese to a platform that showcased and promoted the performances from various races in Singapore. After Tourism Promotion Board began to play a bigger role in Chingay, Chingay was increasingly focused on attracting tourists and its commercialization. Additionally, the government also made use of the parade to promote some of their policies or instil some ideology to its people to achieve its political demands. This paper attempts to understand the historical development of the Chingay Parade through the organization and analysis of past literature and primary sources. Additionally, this paper also explores the different periods of the Chingay Parade to allow the comprehension as to why more and more Singaporeans have become gradually indifferent towards the development of Chingay Parade. Lastly, this paper will offer some insights and suggestions as to the future direction of the Chingay Parade.